Halal certification assistance through sociopreneurship education for MSMEs in Tukak Village - Mei Wulan Sari; Sisi Pitriyana; Tri Ardiansyah; Nur Husnun Fauzizah; Januari Aisora; Iqbal Nur Rifki; Komala Sabrina; Irna Santika; Dewi Safitri; Salsabillah Dhiva Ardhana; Bayu Aditya Saputra (Community Empowerment, 2023)
Tukak Village has abundant marine product potential and there are several MSMEs that focus on developing marine product processing businesses, one of which is kemplang. Not many kemplang products are halal certified due to lack of awareness and information obtained by business actors so that their market coverage is only at the district level. Halal certification is an important factor in the strategy to increase product sales by providing product halal information as an effort to protect consumers. This community service aims to increase knowledge and facilitate applications for halal certification. The program was carried out with the concept of sociopreneurship education through outreach and assistance to six MSMEs. The result of the program shows an increase in knowledge and awareness of MSME actors about the importance of halal certification for their products. Apart from that, all MSMEs have succeeded in producing halal certification application documents and have submitted them to the Indonesian Ulema Council.